2016
DOI: 10.1088/2053-1583/3/1/011004
|View full text |Cite
|
Sign up to set email alerts
|

High thermal conductivity of hexagonal boron nitride laminates

Abstract: Abstract. Two-dimensional materials are characterised by a number of unique physical properties which can potentially make them useful to a wide diversity of applications. In particular, the large thermal conductivity of graphene and hexagonal boron nitride has already been acknowledged and these materials have been suggested as novel core materials for thermal management in electronics. However, it was not clear if mass produced flakes of hexagonal boron nitride would allow one to achieve an industrially-rele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 15 publications
2
46
0
Order By: Relevance
“…Hexagonal boron nitride is a substrate material for graphene devices with improved in‐plane thermal transport . Recently, Zheng et al demonstrated a membrane of h‐BN laminate with an in‐plane thermal conductivity of 20.0 W m −1 K −1 . Sun et al reported that an acetate cellulose h‐BN film can reduce the hot‐spot temperature by 20 °C, compared to bare quartz chips .…”
Section: Introductionmentioning
confidence: 99%
“…Hexagonal boron nitride is a substrate material for graphene devices with improved in‐plane thermal transport . Recently, Zheng et al demonstrated a membrane of h‐BN laminate with an in‐plane thermal conductivity of 20.0 W m −1 K −1 . Sun et al reported that an acetate cellulose h‐BN film can reduce the hot‐spot temperature by 20 °C, compared to bare quartz chips .…”
Section: Introductionmentioning
confidence: 99%
“…The hexagonal boron nitride nanostructures have received research interest due to their supreme electrical, chemical and mechanical properties. In some aspects, hBN holds advantages over its analogue graphene like electrical insulation with large band gap, [1] thermal and chemical stabilities, high thermal conductivities [2], [3] and comparable mechanical properties. [4] These remarkable properties have made hBN nanostructures to have many potential applications in engineering fields.…”
Section: Introductionmentioning
confidence: 99%
“…102 In addition, pure laminates of h-BN could be prepared by vacuum ltration of the h-BN dispersion prepared via liquid exfoliation in IPA. 103 The thermal conductivity of such insulating laminates reached 20 W m À1 K À1 . By improving the quality of the ake-to-ake interface, the interface thermal resistance decreased and thus enhanced thermal conductivity.…”
Section: Gravitational Force-induced Alignmentmentioning
confidence: 98%